Pengembangan Sistem Aplikasi Raport Berbasis Web di SMK Tiara Bangsa - salsha sri mulya (LPPM STMIK AL MUSLIM, 2024)
Tiara Bangsa Vocational High School is a foundation engaged in education, an institution that requires more integrated data processing of student grades in carrying out learning and learning activities. Currently, the report card assessment at Smk Tiara Bangsa already uses the excel application but in recording student grade data by teachers still using forms and grade books, reporting student grade data to parents / guardians of students who are still inefficient. This method is considered inefficient, so the authors conduct research to help teachers or homeroom teachers to be more practical and efficient. To overcome these problems, the authors intend to develop a web-based report card application system. The report card information system that will be created in this study is using PHP with Visual Studio Code and MySQL database. Data collection conducted by the author for this research by means of observation and interviews.